KEHIDUPAN KEAGAMAAN DAN BUDAYA MAS YARAKAT DIKOTA JAYAPURA PROVINSI PAPUA - Muhammad As'ad (Al-Qalam, 2007)
This research was conducted in Jayapura, Papua. This research aimsto describe the role of traditional government in maintaining socialharmony in Jayapura society. This used qualitative method, where datawas collected by interview. Than, data was analyzed by descriptivequalitative.This research indicates that the traditional government has a goodrole and function in maintaining social harmony in Papua society. Thecharisma of traditional leader (tribal leader) is most important factor.His words will be listened and his order will be obey. The social conflictamong the people or between two tribal could be healed by this triballeader intervention.